Revision of Chinese Oretinae (Lepidoptera, Drepanidae) - Song, Wenhui; Xue, Dayong; Han, Hongxiang (Zootaxa, 2012)
The subfamily Oretinae from China is revised. Three genera and thirty species are reported from China. One new species Oreta inflativalva sp. nov. is described. Fourteen new synonyms are established: Oreta obtusa dejeani Watson (= Oreta sinuata Chu & Wang, syn. nov. = Oreta asignis Chu & Wang, syn. nov.); Oreta speciosa (Bryk) (= Oreta hyalina Chu & Wang, syn. nov.); Oreta shania Watson (= Oreta bimaculata Chu & Wang, syn. nov., = Oreta cera Chu & Wang, syn. nov.); Oreta flavobrunnea Watson (= Oreta dalia Chu & Wang, syn. nov.); Oreta pavaca pavaca Moore (= Oreta zigzaga Chu & Wang, syn. nov.); Oreta pavaca sinensis Watson (= Oreta fusca Chu & Wang, syn. nov., = Oreta unichroma Chu & Wang, syn. nov., = Oreta lushansis Fang, syn. nov.); Oreta trispinuligera Chen (= Oreta ankyra Chu & Wang, syn. nov.); Oreta hoenei hoenei Watson (= Oreta trianga Chu & Wang, syn. nov.); Spectroreta hyalodisca Hampson (= Spectroreta fenestra Chu & Wang, syn. nov.); Neoreta brunhyala (Shen & Chen) comb. nov. (= Spectroreta thumba Xin & Wang, syn. nov.). The generic name Neoreta Warren, 1897 is revived for Amphitorna Turner, 1911. Four species are newly recorded for China. The female genitalia of Oreta liensis and Oreta angularis are described for the first time. Three misidentifications in Chu & Wang (1987) are corrected. Diagnoses for the subfamily, genera, and all species are provided. Illustrations of the adults and genitalia are provided.